Power in the Land The Ramsdens and their Huddersfield Estate, 1542−1920 Essays to commemorate the centenary of the purchase of the estate by Huddersfield Corporation in 1920 - Royle, Edward (University of Huddersfield Press, 2020)
In 1542 William Ramsden bought his wife's family home at Longley and so began a long association between the Ramsdens and Huddersfield which lasted until Sir John Frecheville Ramsden sold his greatly increased Huddersfield estate to the Corporation in 1920. This collection of essays is published to commemorate the centenary of that event. Seven local historians examine different aspects of the Ramsden family's relationship with the town and its inhabitants, especially in the nineteenth century.  The book incorporates new research and gives fresh insights into the events which led to Huddersfield becoming 'the town that bought itself' a century ago.